P850 Gender identify and self-reported HPV vaccination among youth living with or at high-risk for HIV. (14th July 2019) - Arnold, Elizabeth; Swendeman, Dallas; Goldbeck, Cameron; Bridges, Kate; Abdalian, Sue Ellen; Klausner, Jeffrey
Abstract : Background: Human Papillomavirus (HPV) is common and is linked to cancer in both males and females. Efforts are underway to increase uptake of the vaccine (Gardasil) that is now recommended for youth and adults up to age 45. However, little is known about the role of gender identify on vaccination, particularly among youth at increased risk for contracting and spreading the virus. Methods: We analyzed data (N=1070) from a longitudinal study of high-risk HIV negative youth and youth living with HIV aged 12–24. Data were collected in Los Angeles, CA and New Orleans, LA from clinic and community settings. We examined self-reports of HPV vaccination as well as predictors of vaccination. Results: Cis-gender females (CGFs) had the highest proportion of youth reporting vaccination (52.7%) followed by transgender youth (45.9%), gender non-conforming youth (44.2%), and MSM (39.0%). Cis-gendered, heterosexual males (CGHMs) reported the lowest proportion (32.9%). However, 18.8% of youth did not know if they had received the vaccine. In our multivariate logistic model examining predictors of vaccination, gender identity was only significant for CGHMs. Other significant variables included age, some education higher than a high school diploma or completing higher education compared to less than high school, ever being tested for Hepatitis C, currently having a healthcare provider, always using condoms, and Latino or other race/ethnicity compared to African-American. Conclusion: Results suggest that despite national efforts to increase the uptake of the vaccine, many youth at high-risk for HPV have not received it or did not know if they had. CGFs appear to have the highest uptake, but CGMs are a group for whom increased efforts targeting vaccination are needed. Demographic and health care factors may also impact vaccination rates. Research is needed on barriers to vaccination and new interventions that go beyond education and promotion such as policy initiatives. Disclosure: No significant relationships.